PERAN SERTA PERKUMPULAN PEMUDA NUSANTARA JAWA SUMATERA (PENJARA) DALAM PENCEGAHAN TERJADINYA TINDAK PIDANA KORUPSI STUDI KASUS DEWAN PIMPINAN PUSAT PERKUMPULAN PEMUDA NUSANTARA JAWA SUMATERA (PENJARA) - Nanda, Satria; Falahiyati, Nurhimmi; Sahbudi, Sahbudi (Universitas Jabal Ghafur, 2024)
One of the most scrutinized crimes in Indonesia is corruption. Corruption in the private sector is as severe as in the public sector, especially when business activities are linked to public sectors such as taxation, banking, and public services. The Nusantara Jawa Sumatera Association, known as